Removal of copper from cattle footbath wastewater with layered double hydroxide adsorbents as a route to antimicrobial resistance mitigation on dairy farms - Gomes, R.L.; Lester, Edward; Hobman, Jon L.; Stekel, Dov J. (Elsevier, 2019)
Copper and zinc are routinely used in livestock antimicrobial footbaths in commercial farming. The footbath mix is a cost to farmers, and the disposal of spent footbath into slurry tanks leads to soil contamination, as well as the potential for antimicrobial metal resistance and co-selection. This study assesses the potential to mitigate a source of antimicrobial metal resistance in slurry tanks while recovering copper and zinc from spent cattle footbaths.